Comments on Fabian Freyenhagen, Adorno's Practical Philosophy. (25th August 2017) - Allen, Amy
Abstract: In this paper, I offer some critical comments on Fabian Freyenhagen's book, Adorno's Practical Philosophy . Although I am largely in agreement with many of his arguments about the value of Adorno's negativism for contemporary critical theory, I raise a few critical questions that are grouped around the following three headings: immanent critique, objectivism, and skepticism. My primary aim in pursuing these questions is not to haggle over fine points of Adorno interpretation but rather to consider how these three issues bear systematically on the vision for critical theory that Freyenhagen has put forward.